Impact of Artificial Intelligence and Human Resource Management on Leadership Organization Perfomance - Fatyandri, Adi Neka; Guo, Bernard; Muchsinati, Evi Silvana (Universitas Merdeka Malang, 2024)
This research was conducted in the manufacturing company sector in Batam. This research aims to find out how much influence artificial intelligence and human resources have on the influence of leadership on organizational performance. The method used in research is a quantitative method. The sample required for this research is 173 respondents. The result of this research is that the research data is free from common method bias because the VIF value is below 5.00. In the convergent validity test, all variables and indicators are said to be valid because the outer loadings value reaches 0.5 which are all variabel are valid because the outer loadings value does meet the criteria. In the Fornell Larcker validity test, the variable average can be said to be valid because there are variables that are less than 0.6, namely organizational performance. Apart from that, in the reliability test all variables are considered reliable exept LEP because the average Cronbach's alpha value is not more than 0.6 and meets the established criteria. For future research may concentrate on other industries, particularly the manufacturing sector, exploring different variables.